Survival and chipping of zirconia-based and metal-ceramic implant-supported single crowns - Kappel, Stefanie; Schröder, Christin; Hassel, Alexander J.; Bömicke, Wolfgang; Rammelsberg, Peter (Clinical implant dentistry and related research, 2012)
Purpose: The objective of this retrospective study was to compare the incidence of chipping of implant-supported, all-ceramic, and metal-ceramic single crowns. Material and Methods: One hundred fifty-three patients (51.7% male, mean age 55.0 years) received 232 cemented implant-supported single crowns. One hundred and seventy-nine crowns had a metal framework (gold alloy) and 53 crowns were all-ceramic (zirconia framework and glass-ceramic veneer material). Age, gender, kind of cementation, and location of the restorations were assessed as possible factors affecting chipping. Results: During the observation period of up to 5.8 years (mean 2.1 years; standard deviation 1.4), a total of 13 (24.5%) all-ceramic and 17 (9.5%) metal-ceramic crowns suffered from chipping, a difference that was statistically significant. A total of ten single crowns had to be remade resulting in survival of 86.8% (all-ceramic) and 98.3% (metal-ceramic). The other possible factors did not have a significant effect on the chipping. Conclusion: Chipping was found to be more frequent for all-ceramic implant-supported single crowns. If the reasons for the vulnerability of all-ceramic crowns remain unknown, implants with all-ceramic single crowns should generally be recommended with care.
First published: 10 October 2011
Gesehen am 05.06.2018